New Syllabus Primary Mathematics - Dr Foong Pui Yee (Oxford university press, 2022)
The New Syllabus Primary Mathematics (NSPM) series is crafted to engage young learners with a student-centered approach, ensuring they build a solid foundation in mathematics. The series features a child-friendly design that introduces new concepts progressively and makes learning enjoyable. Each chapter begins with a Chapter Opener to spark curiosity and includes Recap sections to help students recall previously learned material. The In Focus segments promote discussions around learning objectives, while Let$1 (Bs Learn uses the Concrete-Pictorial-Abstract method to introduce new ideas. Activity Time incorporates collaborative activities and games to enhance skills and knowledge, and Practice provides immediate feedback. Additionally, Mind Workout challenges students with non-routine problems, the Maths Journal encourages reflection on their learning journey, and Self Check enables them to track their progress independently.s
Keywords: Textbook Maths